FIPRONIL AND IMIDACLOPRID REDUCE HONEYBEE MITOCHONDRIAL ACTIVITY - Nicodemo, Daniel [UNESP]; Maioli, Marcos A. [UNESP]; Medeiros, Hyllana C. D. [UNESP]; Guelfi, Marieli [UNESP]; Balieira, Kamila V. B. [UNESP]; De Jong, David; Mingatto, Fabio E. [UNESP] (Wiley-Blackwell, 2014)
Bees have a crucial role in pollination; therefore, it is important to determine the causes of their recent decline. Fipronil and imidacloprid are insecticides used worldwide to eliminate or control insect pests. Because they are broad-spectrum insecticides, they can also affect honeybees. Many researchers have studied the lethal and sublethal effects of these and other insecticides on honeybees, and some of these studies have demonstrated a correlation between the insecticides and colony collapse disorder in bees. The authors investigated the effects of fipronil and imidacloprid on the bioenergetic functioning of mitochondria isolated from the heads and thoraces of Africanized honeybees. Fipronil caused dose-dependent inhibition of adenosine 5'-diphosphate-stimulated (state 3) respiration in mitochondria energized by either pyruvate or succinate, albeit with different potentials, in thoracic mitochondria; inhibition was strongest when respiring with complex I substrate. Fipronil affected adenosine 5'-triphosphate (ATP) production in a dose-dependent manner in both tissues and substrates, though with different sensitivities. Imidacloprid also affected state-3 respiration in both the thorax and head, being more potent in head pyruvate-energized mitochondria; it also inhibited ATP production. Fipronil and imidacloprid had no effect on mitochondrial state-4 respiration. The authors concluded that fipronil and imidacloprid are inhibitors of mitochondrial bioenergetics, resulting in depleted ATP. This action can explain the toxicity of these compounds to honeybees. (c) 2014 SETAC
Keywords: Pesticide; Toxicity mechanism; Insecticide; Honeybee; Mitochondria